Patriotic betrayal the inside story of the CIA's secret campaign to enroll American students in the crusade against communism - Paget, Karen M. (Yale University Press, 2015)
In this revelatory book, Karen M. Paget shows how the CIA turned the National Student Association into an intelligence asset during the Cold War, with students used-often wittingly and sometimes unwittingly-as undercover agents inside America and abroad. In 1967, Ramparts magazine exposed the story, prompting the Agency into engineering a successful cover-up. Now Paget, drawing on archival sources, declassified documents, and more than 150 interviews, shows that the Ramparts story revealed only a small part of the plot.